Bladder contractility index changes with short-term antimuscarinic therapy in patients with detrusor overactivity: A placebo controlled randomised study - Alka Ashok Bhide; Bernadette Lemmon; Philip Rahmanou; G.A. Digesu; Vik Khullar (Continence, 2023)
Aims:: Bladder contractility is altered by high doses of anticholinergics. It is unknown if anticholinergics at doses used for treating overactive bladder alter bladder contractility. This is a randomised, double-blind, placebo controlled cross-over multicentre study with two 2-week treatment periods. Patients with a previous diagnosis of detrusor overactivity and reporting urinary frequency of at least seven times a day, one or more episodes of urge urinary incontinence per week and at least seven episodes of urgency per week were included. Methods:: After a two-week washout period, subjects were randomised to receive propiverine 20 mg od, propiverine 15 mg tds, oxybutynin 5 mg tds or placebo for 2 weeks. After a second washout period, they were randomised to receive 2 weeks of another treatment not previously used. Ambulatory urodynamic monitoring was performed according to ICS standards for 4 h, using a standardised protocol before and after treatment. The bladder contractility index (BCI) was given by the formula: BCI = PdetQmax+ 5Qmax. The main outcome measure was the average BCI for the first 2 voids for each of the treatment. Results:: 77 participants were recruited. The average BCI for the first two voids was 143 (range 24–314). The BCI was not statistically different before and after antimuscarinic therapy or placebo although there were reductions in urinary frequency and urgency over placebo indicating efficacy over placebo in the treatment of detrusor overactivity. Conclusions:: The bladder contractility index did not change significantly in response to antimuscarinic therapy despite a therapeutic effect. This suggests efficacy is mediated by an effect on another system such as sensory rather than motor function.